Wymogi higieniczno-sanitarne sprzedaży bezpośredniej żywności wobec aktualnych oczekiwań - aspekty prawnoporównawcze - Kapała, Anna (Wydawnictwo Naukowe UAM, 2014)
Hygiene and sanitary requirements for direct food sales in light of the current market expectations – aspects of a legal comparative analysis S u m m a r y The paper aims to assess the extent to which the Italian legislative has used the powers vested to it by the EU regulations with regards the national measures applicable in the area of hygiene. The analysis of this issue goes beyond the determination whether domestic provisions have been issued, and seeks to establish whether such provisions, if do exist, facilitate direct sales, ensuring at the same time the maintenance of public health. Domestic measures available in Italian legislation on food hygiene have been described with regards to different forms of direct sale. The analysis has shown that wherever possible, derogations from the EU sanitary and hygiene requirements have been made (within the scope of direct sales in small quantities and traditional production methods), or the hygiene requirements have been reconciled with the specifics of the environment (agro-tourism), while at the same time efforts have been made to ensure food safety in Italy also in compliance with the EU guidelines.

I requisiti igienico-sanitari per la vendita diretta degli alimenti di fronte alle attuali aspettative – aspetti giuridici comparati R i a s s u n t o L’obiettivo dell’articolo è quello di tentare una valutazione di come il legislatore italiano usufruisce delle competenze lasciategli dalle regolazioni dell’Ue, al fine di determinare le misure nazionali in materia di igiene. Si tratta non solo di stabilire se siano state emesse le norme nazionali, ma anche se esse agevolino la vendita diretta, garantendo al. contempo la sicurezza della salute pubblica. Nell’articolo sono state considerate da vicino le misure nazionali previste dal legislatore italiano in materia di igiene alimentare rispetto alle varie forme di vendita diretta. Le considerazioni svolte mostrano che il legislatore italiano ha intrapreso nelle aree in cui ha avuto tale possibilità, le azioni volte ad introdurre deroghe ai requisiti igienicosanitari dell’Ue (in materia di forniture dirette di piccole quantità e di metodi tradizionali di produzione), nonché a conciliare i requisiti igienici con la specificità ambientale (agriturismo), avendo anche cura di garantire la sicurezza alimentare e di prendere in considerazione le linee guida dell’Ue.